Reshoring in Italy: A recent analysis - Giuseppina Talamo; Michele Sabatino (Contemporary Economics, 2018)
This paper contributes to the emerging literature on reshoring by analysing this return strategy in Italy with a focus on economic resilience. The joint analysis of reshoring and economic resilience is a missing link which could shed some light on the evolution of regional and international strategies and could help to understand whether there is a relationship between reshoring and the resilience of Italian industrial districts. In this regard, we intend to understand the behaviour of companies which have carried out reshoring strategies and their links with the territorial and regional area, and hence the economic resilience of the Italian regions in the face of most recent economic and financial shocks, which has contributed to these types of business and production choices. The aim is to demonstrate whether there is a relationship at regional level between companies which have made reshoring choices and the degree of economic resilience of an area. Using recent data, findings suggest that the renewal of supply chain strategy through reshoring can enhance the value of Italian production by a changing business model.
Keywords: F2; F23; L10; O14; 330; reshoring; back-shoring; back-reshoring; offshoring; resilience; productive district